Interactional practices accomplished by index-finger pointing directed at the addressee in Hebrew face-to-face interaction - Inbar, Anna (Frontiers in Psychology, 2025)
This study uses Hebrew data to examine the practices accomplished by index-finger pointing toward the addressee, with a focus on interactional purposes beyond merely indexing the reference. The data were taken from the Haifa Multimodal Corpus of Spoken Hebrew, which consists of video recordings of naturally occurring casual conversations collected between 2016 and 2023. By employing the methodologies of interactional linguistics and multimodal conversation analysis, the study elaborates on the social actions that are accomplished via this gesture, showing that pointing at the addressee in Hebrew talk-in-interaction can be explained from different perspectives. The study suggests that non-referential pointing primarily serves as an attention-drawing device. However, similar to other gestural or verbal attention-drawing devices, in some contexts, the gesture can also be considered to be a cue whereby conveying a negative stance or displaying epistemic authority is recognized. Additionally, it can be employed as an abrupt way of interrupting or as an attempt to elicit a response from the addressee.